2019
DOI: 10.17509/jsl.v2i2.13271
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Students’ Creativity through STEM Project-Based Learning

Abstract: In some school, teacher-centered is commonly found in the learning process. The learning process itself is still in the form of direct transfer of knowledge from teacher to students. Actually, students will learn better if they are engaged in meaningful learning activity.  STEM project-based learning is one of alternative teaching strategies that engaged students in meaningful learning. The aim of this study is to investigate the impact of STEM project-based learning on students' creativity in the topics of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 14 publications
5
78
0
15
Order By: Relevance
“…Existing empirical studies have shown that taking a project-based approach to STEM learning can help foster creativity in students (Hanif et al, 2019;Siew et al, 2015). However, in these research studies, little is reported on the positive effects of this integrated approach on the trait dimension of scientific creativity at the elementary school level.…”
Section: Research Purpose and Hypothesesmentioning
confidence: 99%
“…Existing empirical studies have shown that taking a project-based approach to STEM learning can help foster creativity in students (Hanif et al, 2019;Siew et al, 2015). However, in these research studies, little is reported on the positive effects of this integrated approach on the trait dimension of scientific creativity at the elementary school level.…”
Section: Research Purpose and Hypothesesmentioning
confidence: 99%
“…If creativity is combined with learning and technology will produce high quality work. In a recent study showing that technology enables students to build several media that can help them produce high quality work in the context of creativity (Hanif et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Creativity is the result of interactions between individuals and their environment (Munandar, 2014). Creativity is one of the 21st century skills needed by students in facing technological advancements and their future career preparation (Bell, 2010;Hanif et al, 2019). Creativity can be defined as a set of strong mental activity abilities to generate or recognize ideas, alternatives, or possibilities that might be useful in solving problems, communicating with others, and entertaining ourselves and others (Al-Oweidi, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Research that has been done shows that the application of STEM in learning can improve creative thinking skills (Henriksen, 2014;Ugras, 2018;Yasin, Prima, & Sholihin, 2018;Apriyani, Ramalis, & Suwarma, 2019;Hanif, Wijaya, & Winarno, 2019), preparing students to develop the skills needed in 21st century education (Sanders, 2009), has a significant effect on increasing student achievement (Becker & Park, 2011), effectively applied in the learning process and achieving learning objectives (Borchers, El-Sayed, & Hoff, 2012), scientific investigations and the discovery of biological content (Osman, Hiong, & Vebrianto, 2013), are able to instill creative problem solving techniques in students and development future innovators (Roberts, 2012), increase student innovation and learning outcomes (Ceylan & Ozdileka, 2014), enhance metacognitive skills and student interest in science lessons (Anwari et. al., 2015), create concrete and meaningful learning (Le et al, 2015) as well as learning outcomes and scientific process skills (Saraç, 2018).…”
Section: Introductionmentioning
confidence: 99%